PENDIDIKAN PERSPEKTIF ISLAM REKONSTRUKSIONISME - Muhammad Hajirin Nur; Rahmat Soe'oed; Khojir Khojir (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2022)
The friction between eastern and western cultures that occurs and influences each other has implications for the friction between Islamic education and global culture. The touch of global culture causes socio-cultural changes and local wisdom values. Modernization and globalization have built and introduced new values in Islamic thought and philosophy. In the context of the perspective of the philosophy of Islamic education, the school of reconstructionism is a school that seeks to overhaul the old order by building a modern pattern of cultural life, as well as trying to find agreement among human beings. The flow of reconstructionist philosophy influences and brings changes to the construction of Islamic education. This paper aims to examine issues related to education from an Islamic perspective on reconstructionism using library research with a qualitative research approach and descriptive-analytical methods. This study concludes that it is necessary to reconstruct Islamic education in various aspects and turn every challenge it faces into an opportunity so that progress, independence, and existence remain and can survive amidst the challenges of the times.